Significance Of Historical Monuments In Kashkadarya Region In Ancient Sources (Eurasian Journal of History, Geography and Economics, 2025)
This article talks about the coverage in written sources of ancient cities and historical and architectural monuments located in different regions of our country. The topic is studied using the example of old cities and historical monuments of the Kashkadarya region.